A scoping review on disparities in exposure to advertising for e-cigarettes and heated tobacco products and implications for advancing a health equity research agenda - Graziele Grilo; Elizabeth Crespi; Joanna E. Cohen (BMC, 2021)
Abstract Background Disparities in exposure to and density of tobacco advertising are well established; however, it is still unclear how e-cigarette and heated tobacco product (HTP) advertising vary by age, education, sex, gender identity, race/ethnicity, sexual orientation, socioeconomic status (SES), and/or urban/rural area. Through a scoping review, we sought to identify potential disparities in exposure to e-cigarette and HTP advertising and promotion across populations. Methods In January 2020, a systematic literature search was conducted in five databases: PubMed, Scopus, Embase, Web of Science, and the Cochrane Library. The search was updated in October 2020. Articles reporting on exposure to e-cigarette and/or HTP advertising and promotion across age, education, sex, gender identity, race/ethnicity, sexual orientation, SES, and/or urban/rural areas were included for full-text review (n = 25). Of those, 15 were deemed relevant for data extraction. Results The majority of the studies were from the U.S. (n = 12) and cross-sectional (n = 14). Studies were published between 2014 and 2020 and focused on determining causal relationships that underlie disparities; only one study assessed HTP advertising and promotion. Exposure to e-cigarette and HTP advertising was assessed at the individual-level (e.g., recall seeing ads on television) and at the neighborhood-level (e.g., ad density at the point-of-sale). Studies addressed differences across age (n = 6), education (n = 2), sex (n = 6), gender identity and sexual orientation (n = 3), race/ethnicity (n = 11), SES (n = 5), and urban/rural (n = 2). The following populations were more likely to be exposed to e-cigarette advertising: youth, those with more than a high school diploma, males, sexual and gender minorities, Whites, and urban residents. At the neighborhood-level, e-cigarette advertisements were more prevalent in non-White neighborhoods. Conclusions Exposure to e-cigarette/HTP advertising varies based on sociodemographic characteristics, although the literature is limited especially regarding HTPs. Higher exposure among youth might increase tobacco-related disparities since it can lead to nicotine/tobacco use. Research should incorporate and apply a health equity lens from its inception to obtain data to inform the elimination of those disparities.